THE IMPACT OF RURAL WOMEN PARTICIPATION IN AGRICULTURAL ACTIVITIES IN NIGERIA: A STUDY OF KUSTIM WOMEN 2013 - GUMAR MANJI KEFAS; GREGORY GOTULGOTOM; IFEAGWU CHRISTOPHER UCHECHUKWU (International Studies Journal)
Agriculture is the cornerstone of many African economics especially in sub-Saharan Africa.  It provides a relatively large portion of the Gross Domestic product (GDP) in Sub-Saharan African.  And it is also the main source of foreign currency.  Agriculture is important to thee Economic Growth of most Nigeria’s societies. It is also the principal source of food and livelihood in the rural areas. The study is centered on women participation in agricultural activities.  The research is set to investigate the impact of women participation in Agricultural activities study of Kustium Women2013 -2023.